BRS Deméter: new malting barley cultivar for irrigated Brazilian savanna - Amabile, Renato Fernando; Minella, Euclydes; Guerra, Antonio Fernando; Silva, Dijalma Barbosa da; Albrecht, Júlio César; Antoniazzi, Noemir (Pesquisa Agropecuaria Brasileira, 2008)
BRS Deméter is a spring, two-rowed barley, widely adapted to irrigated areas of the savanna, in Central Brazil. It presents production stability and high malting quality, with yield potential above 5,000 kg ha-1. It fulfills both the farmer and malting industry expectations regarding competitive yield and brewing quality.